Evidence Against a Perihemorrhagic Penumbra Provided by Perfusion Computed Tomography - Christian Herweh; Eric Jüttler; Peter D. Schellinger; Ernst Klotz; Ekkehart Jenetzky; Berk Orakcioglu; K. Sartor; Peter Schramm (2007)
Several recent studies analyzing perfusion changes in acute intracerebral hemorrhage fed the debate whether there is secondary ischemic tissue damage in the vicinity of intracerebral hemorrhage. We used perfusion CT to address this question.We examined 36 patients between 2001 and 2002 with acute intracerebral hemorrhage (within 24 hours after symptom onset). A subgroup of 8 patients was examined serially on day 1, between days 2 and 4, and after day 5. Nonenhanced CT images and maps of cerebral blood flow, cerebral blood volume, and time to peak were evaluated by region of interest analysis.In comparison to the contralateral hemisphere, perfusion values were clearly reduced around the hematoma (relative values: cerebral blood flow 0.51, cerebral blood volume 0.62, time to peak 1.7 seconds). There was no difference in size between the area of reduced perfusion and the area of edema (5.17 versus 5.75 cm(2), respectively) surrounding the hematoma. At time point 2, the edema grew significantly.In accordance with previous studies, we found reduced perfusion as well as edema surrounding acute intracerebral hemorrhage. Regarding ischemic tissue damage, we did not detect an initial mismatch between the perfusion deficit and the edema and therefore could not identify any tissue at risk of ischemia. We therefore interpret the reduced perfusion as a secondary phenomenon, ie, reduced oxygen demand of tissue damaged by pressure and clot components, not as the cause of any tissue damage associated with acute intracerebral hemorrhage.